2019
DOI: 10.1016/j.jmathb.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Improving realistic word problem solving by using humor

Abstract: Research has shown that children have a strong tendency to exclude real world considerations when solving word problems. In this study, we investigated a novel way to try to change this tendency. We tested whether children would adapt their behavior when solving word problems in which realistic considerations are required (P-items) when these problems are embedded in a humoristic context as compared to when they are offered in a typical word problem solving context. 148 sixth graders solved four P-items in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
0
23
0
3
Order By: Relevance
“…Based on the results of the study, it appears that learning activities greatly affect problem-solving abilities, this is by the concept of learning activities which are a process of behavior change that is very influential in ongoing learning (Apriandi, 2012;Sariayu & Miaz, 2020;Widodo, 2014). The use of learning activities to motivate students to enthusiastically participate in learning activities will have a good impact on problem-solving abilities (Choi et al, 2014;Dooren et al, 2019). This is supported by research, showed an increase in students' understanding of mathematical concepts by using activity sheets by students (Ningsih, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the study, it appears that learning activities greatly affect problem-solving abilities, this is by the concept of learning activities which are a process of behavior change that is very influential in ongoing learning (Apriandi, 2012;Sariayu & Miaz, 2020;Widodo, 2014). The use of learning activities to motivate students to enthusiastically participate in learning activities will have a good impact on problem-solving abilities (Choi et al, 2014;Dooren et al, 2019). This is supported by research, showed an increase in students' understanding of mathematical concepts by using activity sheets by students (Ningsih, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps not surprisingly, having students actually work with the materials of a problem (Reusser & Stebler, 1997b) or perform the task in the problem (DeFranco & Curcio, 1997) improved sense‐making. Interestingly, interleaving jokes about math class and word problems in between the problematic problems has been shown to improve realistic responses as well (Van Dooren, Lem, De Wortelaer, & Verschaffel, 2019).…”
Section: Interventions To Improve Student Sense‐makingmentioning
confidence: 99%
“…The Realistic Mathematical Education (RME) approach has several advantages: making mathematics learning more meaningful, less formal, not too relevant, and more interesting (Arsaythamby & Zubainur, 2014;Bosica et al, 2021). In addition, this approach considers the level of student ability, emphasizes learning mathematics in learning by doing, facilitates solving mathematical problems, and uses context as a starting point for learning mathematics (Dooren et al, 2019;Zandieh & Rasmussen, 2010). This will make students not feel bored so that the learning delivered will be more memorable, and the concepts implanted by the teacher will be remembered longer by students.…”
Section: Introductionmentioning
confidence: 99%